2021
DOI: 10.3390/electronics10121433
|View full text |Cite
|
Sign up to set email alerts
|

Smart-Object-Based Reasoning System for Indoor Acoustic Profiling of Elderly Inhabitants

Abstract: Many countries are facing significant challenges in relation to providing adequate care for their elderly citizens. The roots of these issues are manifold, but include changing demographics, changing behaviours, and a shortage of resources. As has been witnessed in the health sector and many others in society, technology has much to offer in terms of supporting people’s needs. This paper explores the potential for ambient intelligence to address this challenge by creating a system that is able to passively mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…This demands urgent innovations capable of breaking through the reluctance of the elderly to accept and use new technologies, both stationary products used at home and wearable devices (wearables) for when on the move [19], and finding workarounds to constraints in the form of additional cost, inconveniences, social constraints, or privacy issues by utilizing existing standard equipment, such as in the analysis of wi-Fi signal equivalents for the movement of people [20] or even smart TV usage [21]. Passive technologies working in the background, such as the analysis of sound patterns in rooms [22], radio frequency identification (rFID) [23], floor vibration detectors [24], thermal and air quality sensors [25,26], are to be preferred to active monitoring, like video surveillance, which are often considered too intrusive [20]. The best results are achieved when several sensing technologies are combined into a single integrated system [23].…”
Section: Resultsmentioning
confidence: 99%
“…This demands urgent innovations capable of breaking through the reluctance of the elderly to accept and use new technologies, both stationary products used at home and wearable devices (wearables) for when on the move [19], and finding workarounds to constraints in the form of additional cost, inconveniences, social constraints, or privacy issues by utilizing existing standard equipment, such as in the analysis of wi-Fi signal equivalents for the movement of people [20] or even smart TV usage [21]. Passive technologies working in the background, such as the analysis of sound patterns in rooms [22], radio frequency identification (rFID) [23], floor vibration detectors [24], thermal and air quality sensors [25,26], are to be preferred to active monitoring, like video surveillance, which are often considered too intrusive [20]. The best results are achieved when several sensing technologies are combined into a single integrated system [23].…”
Section: Resultsmentioning
confidence: 99%
“…In answering RQ2, the searches and screening process resulted in thirteen articles to be critically appraised. Twelve [46][47][48][49][50][51][52][53][54][55][56][57] of the thirteen studies demonstrated medium to high quality, as the twelve studies had information to answer all criteria in the MMAT, with the thirteenth [56] study falling short of answering S2 and the rest of the criteria. The research hypothesis of these twelve studies was clear and relevant, focusing on vibration and/or acoustic sensing technologies in monitoring human activities.…”
Section: Critical Appraisal and Overview Of Studies Includedmentioning
confidence: 99%
“…Those involving sensor development used dummy models, dolls, or human actors for sampling. The only mixed-methods study [49] included a qualitative human focus group study to inform model development using parameters identified. Issues with missing data were not observed for the mixed-method study.…”
Section: Critical Appraisal and Overview Of Studies Includedmentioning
confidence: 99%
See 2 more Smart Citations